Multi-Heuristic Based Technique in Multi-SVCs Installation Scheme for Loss Control in Transmission System - et. al., Shahrizal Jelani, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Increasing demand of power system has been identified as one of the dominant factors in under-voltage phenomenon, instability condition and increment of transmission loss in power system. To alleviate this condition for the purpose of maintaining secure delivery of electricity, appropriate remedial actions are mandatory to be performed in either real time or offline studies. Amongst the popular remedial actions to avoid the loss control is the installation of static VAR compensator (SVC) scheme. This scheme requires a robust optimization technique which should be able to achieve optimal solution with less computation burden. This paper presents the application of multi-heuristic techniques for optimizing the sizing and locations of the SVC installation. Two optimization techniques are proposed in this study; namely the evolutionary programming (EP) and artificial immune system (AIS) for the purpose of optimal determination of locations and sizing of SVCs. Several cases are considered, based on number of units for the installation process; solved under different loading conditions subjected to the system. A reliability test system (RTS) model was utilized as the test specimen in this study; which ultimately highlights the merit of the optimization techniques.